PRÁTICAS INOVADORAS DE GESTÃO POR COMPETÊNCIAS EM ORGANIZAÇÕES PRIVADAS BRASILEIRAS - Salomão, Aretha Henrique Martins; Chagas, Melina Medeiros das; Marques, Nayara Baptista (Revista Valore, 2022)
PRÁTICAS INOVADORAS DE GESTÃO POR COMPETÊNCIAS EM ORGANIZAÇÕES PRIVADAS BRASILEIRAS